Data Breach In Indonesia: A Contemporary View - Jauhar Rizqullah Sumirat (Innovative: Journal Of Social Science Research, 2023)
Data protection is then needed to ensure data security from this, one of which is data breach. The first ever internet-related data breach occurred in 2005 when more than 1 million records of 1.4 million credit card accounts registered with the DSW Shoe Warehouse were leaked. Data breach cases in Indonesia are not small. Over the past two years, people's personal data has been leaked, ranging from data belonging to e-commerce companies such as Lazada and Tokopedia to data belonging to government organizations such as the Healthcare and Social Security Agency and the General Elections Commission. Data Breach is a complex crime, and it only happened in Indonesia recently, which has made it a concern. The Indonesian government also became reactive to this and immediately passed the Personal Data Protection Law as the legal basis for data protection in Indonesia. This is a concrete step by the government to handle data breach cases in Indonesia. Simultaneously with the case of Bjorka who had committed a data breach on several government bodies, the government also formed a task force to handle the case. Keynote: Data, Indonesia, Contemporary